Essential Oils as Dermocosmetic Agents, Their Mechanism of Action and Nanolipidic Formulations for Maximized Skincare - Shamama Javed; Bharti Mangla; Ahmad Salawi; Muhammad H. Sultan; Yosif Almoshari; Waquar Ahsan (Cosmetics)
Essential oils (EOs) are known for their diverse bioactivities, including antioxidant, anti-inflammatory, antibacterial, antifungal, antiviral, skin-barrier repairing and anticancer, and therefore, hold profound potential to be used in cosmetic and skincare products. Owing to these properties, EOs have long been utilized to address a range of dermatological issues, from acne and inflammation to aging and dryness. However, problems associated with EOs beset their practical applications, which include high volatility, oxidation, hydrophobic nature, low bioavailability, skin irritation, chemical transformation and poor stability in air and light. A prospective of nanolipidic formulations, including the nanostructured lipid carriers (NLCs) and solid lipid nanoparticles (SLNs) system for improved skin delivery of these EOs highlights the possibility of their use in topical applications, which offer several advantages such as improved bioavailability and stability, lower toxicity and higher drug content. These nanoformulations protect the EOs from environmental degradation and improve their penetration into deeper skin layers, leading to prolonged therapeutic benefits. The delivery of bioactive agents using a conventional topical preparation exhibits low penetration, frequent applications, poor adherence and prolonged therapy duration, whereas the novel delivery system exhibits improved stability of the drug, enhanced skin penetration, enhanced retention and better therapeutic efficacy. This review provides a comprehensive compendium of information on EOs, which are widely used in skincare, along with their nanolipidic formulations for maximized skincare uses. The mechanism of action of EOs as skin bioactive agents, challenges associated with their use, advances in nanolipidic formulations and their market value as cosmetic skincare products are also explored.